Informality, Consumption Taxes, and Redistribution - Bachas, Pierre; Gadenne, Lucie; Jensen, Anders (Review of Economic Studies, 2024)
Abstract Can taxes on consumption redistribute in developing countries? Contrary to consensus, we show that taxing consumption is progressive once we account for informal consumption. Using household expenditure surveys in 32 countries, we proxy for informal consumption using the type of store where purchases occur. We establish that the budget share spent in informal stores steeply declines with income, so that richer households pay a substantially larger share of their income in taxes. Our findings imply that the widespread policy of exempting food from taxation is hard to justify on equity grounds in low-income countries.